2009
DOI: 10.1007/s10526-009-9220-2
|View full text |Cite
|
Sign up to set email alerts
|

Antimycotic activities of Cinnamon-derived compounds against Rhizoctonia solani in vitro

Abstract: In this study, the effects of medicinal plant extracts on the development of mycelium in the following phytopathogenic fungi were evaluated: Phytophthora capsici, Rhizoctonia solani, Fusarium solani, Colletotrichum gloeosprorioides, and Botrytis cinera. Of the 26 medicinal plants tested, six plant extracts showed antifungal activity against phytopathogenic fungi. The highest antifungal activity was exerted against R. solani by the n-hexane fraction of a Cinnamon (Cinnamomum cassia Blume) solvent extract. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 19 publications
2
15
0
4
Order By: Relevance
“…This might be due to the flavonoid sulfates which inhibits the mosquito larvae alterations in the spiracular valves of the siphon and anal papillae [33,34] . The presence of phenols and reducing sugars are proved to have potential mosquito larvicidal activity [35] . Phenolic groups are highly hydroxylated which includes flavonols, hydroxycoumarins, hydroxycinnamate derivatives, flavanols, flavanones, anthocyanins, proanthocyanidins, hydroxystilbene, aurones etc.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to the flavonoid sulfates which inhibits the mosquito larvae alterations in the spiracular valves of the siphon and anal papillae [33,34] . The presence of phenols and reducing sugars are proved to have potential mosquito larvicidal activity [35] . Phenolic groups are highly hydroxylated which includes flavonols, hydroxycoumarins, hydroxycinnamate derivatives, flavanols, flavanones, anthocyanins, proanthocyanidins, hydroxystilbene, aurones etc.…”
Section: Discussionmentioning
confidence: 99%
“…oryzae (bacterial blight). Plant extracts have been tested previously for direct antimicrobial activities against R. solani and B. oryzae (Khoa et al 2011;Sehajpal et al 2009;Nguyen et al 2009;De Rodríguez et al 2007;Harish et al 2007), but only in vitro, thus excluding other possible mechanisms such as induced resistance. On the other hand, Kagale et al (2004) concluded that a leaf extract from Datura metel not only possessed antimicrobial activity against R. solani, but that it was also able to induce systemic resistance in rice.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous study, antibiotics purified from biocontrol agents of bacteria have been shown to be effective in controlling postharvest pathogens (Alemu and Alemu, 2013), such as pyrrolnitrin produced by Pseudomonas cepacia was applied in controls gray and green mold on apples and pears (Rinez et al, 2013). Now, some antifungal compounds have been directly utilized for the biocontrol of fungal pathogens (Nguyen et al, 2009;Zhang et al, 2012;Fan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%